Performance Evaluation of an Integrated Heat Pump Fluidized-Bed Dryer with Solar and Biomass Furnace for Paddy Drying - Yahya, M.; Yuwazama, Zido; Wardianto, Dedi; Pratiwi, Putri; Agusman, Delvis (Program Studi Teknik Mesin Universitas Pamulang, 2026)
This study aims to evaluate the performance of a heat pump fluidized-bed dryer incorporating a biomass furnace and a solar collector for paddy drying. The paddy moisture content (MC) was decreased from 28.52% to 16.28% on a dry basis (db) through the drying process over 23.68 minutes, under operating conditions of a mass flow rate of 0.1033 kg/s and an average temperature of 70 °C. An average drying rate of 0.042 kg/min was achieved, corresponding to a specific moisture extraction rate of 0.24 kg/kWh. Correspondingly, the system required average specific electrical and thermal energy consumptions of 7.43, 3.21, and 4.22 kWh/kg, respectively. The biomass furnace demonstrated a high thermal efficiency of 87.9%, while the solar collector achieved an average efficiency of 31.7%. The heat pump exhibited stable performance, with an average coefficient of performance measured at 3.2. The heat pump condenser, solar collector, and biomass furnace generated average heat energies of 2.37 kW, 0.79 kW, and 2.91 kW, respectively. The dryer exhibited average thermal and pickup efficiencies of 21.8% and 40.4%. The average exergy efficiency was 57.7%. Furthermore, the incorporation of the heat recovery exchanger resulted in an approximate 47% reduction in heat energy consumption.